The Marshall – Olkin Teissier generated model for lifetime data - Eghwerido, Joseph Thomas (Journal of the Belarusian State University. Mathematics and Informatics, 2022)
An accurate mathematical inference depends on the experimental design and the model adopted in the process. Thus, in this study Marshall – Olkin Teissier generated distribution was used to present the distribution of the true nature of lifetime data. The characteristics of the proposed model were examined in a closed form. The behaviour of the new model indicated that the hazard rate of the submodels could be J- and U-shaped, decreasing and increasing. Monte Carlo simulations were presented for different configurations of parameters with varying sizes. The results of the simulation and goodness-of-fit of the real lifetime data show that the Marshall – Olkin Teissier generated model is flexible, tractable and applicable when compared to some classical two parameters distributions.
Keywords: Gompertz distribution; Marshall – Olkin distribution; Teissier generated distributions; Teissier distribution